Dog Owners' Ideas and Strategies Regarding Dental Health in Their Dogs-Thematic Analysis of Free Text Survey Responses - Enlund, Karolina Brunius; Pettersson, Ann; Eldh, Ann Catrine (Frontiers in Veterinary Science, 2022)
Periodontal disease is the most common disease in dogs over three years of age. In dogs, as in humans, daily tooth brushing, as a means of active dental home care, is considered the gold standard for prophylaxis and prevention of periodontal disease progression. However, the performance of adequate tooth brushing is insufficient in dogs. There is no full account as to why dog owners fail to comply with this routine, but in order to facilitate better practice, a further understanding of dog owner’s perspectives is needed. The aim of this study was to investigate dog owners’ ideas and strategies regarding their dogs´ dental. In a large-scale Swedish survey regarding dental health in dogs, dog owners’ free text comments (n = 8 742) from a concluding open-ended query were analyzed using qualitative methods. Many different notions concerning dental health in dogs were identified, of which perceived importance of different diets and chewing being the most prominent. Five common themes represented dog owners’ ideas and strategies regarding dental health in their dogs: what is considered to cause dental problems; what is deemed not to promote dental health; how to prevent dental problems; what impedes proper dental care, and; needs for increased knowledge and support. Contrary to existing research and knowledge in the field, the respondents commonly trusted that diet procure good dental health in the dog, as does chewing on bones. Seemingly, a range of misconceptions flourish among dog owners, indicating a need to share information and experiences, as well as support to bridge barriers to tooth brushing and other aspects that can enhance dog owners’ knowledge and practice. In addition, this study highlights the need for randomized controlled trials on effects of diets and supplements on different aspects of dental health; calculus, periodontal disease, and dental fractures, including dogs of different breeds, sizes and ages. Further research is also needed with respect to which strategies that best aid dog owners, by whom the support is best provided, when, and at what time point.